ANALISIS PENERAPAN TOD DI KAWASAN DUKUH ATAS BNI - Taki, Herika Muhamad; Rafi Rabbani; Wahyunisa Amalia (Jurnal Lingkungan dan Kota, 2025)
This Research analyzes TOD Implementation in Dukuh Atas BNI Area, Jakarta, which multi mode hub transportation that integrates MRT, KRL, LRT, and Transjakarta. A methode is used to qualitative description with GIS Integration to map land use and transportation network. Research result shows that this area has high connectivity level, supporting mixed principle development with integration house facility, commercial, and public space, however, some challenges like crowds arrangement to rush hour and optimilization pedestrian path also bicyle needs to be improved. TOD implementation in this area have shown essential step in admitting sustainable urban area, however infrastructure empowerment and supporting policy need. Dukuh Atas BNI potentially becomes ideal TOD Model in Indonesia with coordinating good crossing sector